NIP/DuoxA is essential for Drosophila embryonic development and regulates oxidative stress response. - Xie, X.; Hu, J.; Liu, X.; Qin, H.; Percival-Smith, A.; Rao, Y.; Li, S.S. (International Journal of Biological Sciences, 2010)
NIP/DuoxA, originally cloned as a protein capable of binding to the cell fate determinant Numb in Drosophila, was recently identified as a modulator of reactive oxygen species (ROS) production in mammalian systems. Despite biochemical and cellular studies that link NIP/DuoxA to the generation of ROS through the dual oxidase (Duox) enzyme, the in vivo function of NIP/DuoxA has not been characterized to date. Here we report a genetic and functional characterization of nip in Drosophila melanogaster. We show that nip is essential for Drosophila development as nip null mutants die at the 1(st) larval instar. Expression of UAS-nip, but not UAS-Duox, rescued the lethality. To understand the function of nip beyond the early larval stage, we generated GAL4 inducible UAS-RNAi transgenes. da(G32)-GAL4 driven, ubiquitous RNAi-mediated silencing of nip led to profound abnormality in pre-adult development, crinkled wing and markedly reduced lifespan at 29 degrees C. Compared to wild type flies, da-GAL4 induced nip-RNAi transgenic flies exhibited significantly reduced ability to survive under oxidative stress and displayed impaired mitochondrial aconitase function. Our work provides in vivo evidence for a critical role for nip in the development and oxidative stress response in Drosophila.